Marketing research of the market of drugs for the treatment of hepatobiliary system diseases in Ukraine during the covid-19 pandemic - Krikliva, Irina; Karpenko, Liliya; Zaporozhska , Svitlana; Saiko Ірина; Sichkar , Antonina (Annals of Mechnikov’s Institute, 2021)
Introduction. Since the beginning of the COVID-19 pandemic, doctors around the world, including Ukraine, have seen an increase in liver disease, which, incidentally, leads to complications of coronavirus infection. This can be both acute liver damage by the virus itself and hepatotoxic effects of medicines used in COVID-19. The treatment of liver and biliary tract diseases remains an urgent task for Ukraine, given the epidemic situation that exists today in the country. The purpose of our research was to study the range of drugs for the treatment of liver and biliary tract diseases registered in the pharmaceutical market of Ukraine since the beginning of the COVID-19 pandemic. Materials and methods. The data of information resources, such as the State Register of Drugs, Compendium of Drugs, etc., which have been generalized by means of marketing methods, structural, statistical, and graphic analyzes, are used in the work. Results and discussion. A special place in the treatment of hepatobiliary pathology is occupied by medicines that belong to the group of hepatoprotectors. There are several classifications of hepatoprotectors. For example, SV Okovytyi proposes to divide hepatoprotectors by origin. According to the classification proposed by ON Minushkin, LV Maslovskyi, AA Bukshuk hepatoprotectors are divided by mechanism of action. Thus hepatoprotectors can be of plant or animal origin, medicines that contain amino acids and essential phospholipids, medicines of synthetic origin. We have analyzed the Ukrainian market of hepatoprotective medicines. The analysis was performed in group A05 "Bile and liver therapy" (according to the ATC classification). Data are for September 2021. Both imported and domestic drugs are represented in the Ukrainian market. A total of 73 trade names of hepatoprotectors have been registered so far. The first place in the number of names of medicines for the treatment of hepatobiliary system diseases, which are on the market of Ukraine, is occupied by Germany, the second - India, and the third - Czech Republic and Canada. In general, hepatoprotective medicines from 16 countries are present on the Ukrainian market. The first place in prevalence is occupied by medicines of plant origin. Second place take ursodeoxycholic acid preparations, and in third place are preparations of essential phospholipids. Solid dosage forms for oral administration (tablets, capsules, granules) occupy more than half of the market of hepatoprotective medicinal products in Ukraine. Most hepatoprotective drugs are over-the-counter. Conclusions. Given the state of treatment of hepatobiliary system diseases, which has not lost its relevance during the COVID-19 pandemic, the situation in the pharmaceutical market in terms of range of hepatoprotectors registered in Ukraine has been analyzed. It is demonstrated that hepatoprotective drugs are widely represented in the pharmaceutical market of Ukraine. The market is saturated with original and generic drugs, medicines of both imported and domestic production are presented; both prescription and over-the-counter drugs in various dosage forms are available. Keywords: hepatobiliary system, liver disease, hepatoprotectors, market analysis DOI: 10.5281/zenodo.5761206